Spiegare gentilmente i passaggi e il ragionamento.
y = a·(x - 2)^2
[0, 2]
2 = a·(0 - 2)^2---> 2 = 4·a--> a = 1/2
y = 1/2·(x - 2)^2--> y = x^2/2 - 2·x + 2
x^2 + y^2 = 4---> y = - √(4 - x^2) ∨ y = √(4 - x^2)
Calcolo area Gialla:
√(4 - x^2) - (x^2/2 - 2·x + 2)
∫(√(4 - x^2) - (x^2/2 - 2·x + 2)) dx =
=2·ASIN(x/2) + x·√(4 - x^2)/2 - x^3/6 + x^2 - 2·x
valutato in x = 2:
2·ASIN(2/2) + 2·√(4 - 2^2)/2 - 2^3/6 + 2^2 - 2·2=
=pi - 4/3
valutato in x = 0
2·ASIN(0/2) + 0·√(4 - 0^2)/2 - 0^3/6 + 0^2 - 2·0=
=0
Quindi:
A (gialla)=pi - 4/3
Altra parte= pi·2^2 - (pi - 4/3) = 3·pi + 4/3